EFEKTIVITAS EKSTRAK Zingiber purpureum DALAM MENURUNKAN KADAR GLUKOSA DARAH PADA TIKUS Rattus norvegicus MODEL OBESITAS - Riki Nova (Yayasan Nusantara Hasana Berdikari, 2025)
This study evaluated the effectiveness of Zingiber purpureum extract in lowering blood glucose levels in obese Rattus norvegicus mice. Twenty mice were divided into five groups (n=4): negative control, positive control, comparison, treatment 1 (P-1; 100 mg/kgBW), and treatment 2 (P-2; 200 mg/kgBW). The treatment was given for 4 weeks. Blood glucose levels were measured before and after treatment. The Kruskal-Wallis test showed significant differences between groups (p=0.005), with the greatest decrease in blood glucose in P-2 (mean Δ=32.25 mg/dL). These results indicate the potential of Zingiber purpureum as an adjuvant therapy to lower blood glucose in obesity.